Geographic Variation in Bryde’s Whale Be4 Calls in the Gulf of California: An Insight to Population Dynamics - Viloria-Gómora, Lorena; Urbán R, Jorge; Leon-Lopez, Braulio; Romero-Vivas, Eduardo (Frontiers in Marine Science, 2021)
Although Bryde's whale (Balaenoptera edeni) has worldwide distribution, it is considered one of the most difficult species of baleen whales to study. Two populations existing in the Gulf of California have been proposed, but difficulties in obtaining biopsies have complicated testing the hypothesis of discrete stock difference between north and south of the Gulf. On the other hand, bioacoustics analyses have been used to differentiate populations from other whale species. Therefore, to provide information for the previously proposed hypothesis, the most common Bryde’s call (Be4) in the region was analyzed. Acoustic data was collected using a High-frequency Acoustic Recording Package (HARP) system placed at two locations in the Gulf of California: one in the north from November 2006 to June 2007 and other one in the south from August to December 2008. Duration and frequency range were measured for calls with a signal-to-noise ratio (SNR) greater than 27 dB. The Mann-Whitney-U test was performed to compare distributions in both geographic areas, and the results were compared with a photo-identification analysis. Of the 903 Be4 calls detected, 103 (north) and 92 (south) met the SNR requirement. Duration showed a significant difference (Mann-Whitney test, U = 11238, z-statistics = 2.91, p = 0.003) with southern calls being longer than the nothern ones. The results suggest that the northern population remains resident in the north with some movement towards the south, also verified by photo-identification. A detailed inspection showed a double distribution in the south (Mann-Whitney test, U = 2211, z-statistics = -8.39, p = 4.4776e-17), suggesting the presence at the same time of resident and transient populations. The latter has been suggested to belong to the Eastern Tropical Pacific. The results suggest a geographic variation in B. edeni Be4 call type and support the existence of two populations within the Gulf of California.